2023
DOI: 10.1038/s42004-022-00803-3
|View full text |Cite
|
Sign up to set email alerts
|

Critical impacts of interfacial water on C–H activation in photocatalytic methane conversion

Abstract: On-site and on-demand photocatalytic methane conversion under ambient conditions is one of the urgent global challenges for the sustainable use of ubiquitous methane resources. However, the lack of microscopic knowledge on its reaction mechanism prevents the development of engineering strategies for methane photocatalysis. Combining real-time mass spectrometry and operando infrared absorption spectroscopy with ab initio molecular dynamics simulations, here we report key molecular-level insights into photocatal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“… The kinetic oxidation model of methane and methane‐derived surface intermediates on the catalyst surface covered with one layer of adsorbed water. The water oxidation process is omitted from the diagram because it is not rate‐determining in the photocatalytic oxidation of methane with water [7b] . a) Kinetic model and b) possible eight‐step reaction pathways and intermediates (X i, i=1–8 shown in Scheme 1a; e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… The kinetic oxidation model of methane and methane‐derived surface intermediates on the catalyst surface covered with one layer of adsorbed water. The water oxidation process is omitted from the diagram because it is not rate‐determining in the photocatalytic oxidation of methane with water [7b] . a) Kinetic model and b) possible eight‐step reaction pathways and intermediates (X i, i=1–8 shown in Scheme 1a; e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the detailed kinetic analyses [7b] provided in Supporting Information Section 4, the observed P CH4 profiles of r CO2 and r C2H6 for the Pt/Ga 2 O 3 photocatalyst under steady‐state reaction conditions could be simply described as the first‐ and second‐order reactions of the initially adsorbed intermediate X 1 as r CO2 ${{\rm { \propto }}}$ θ X1 and r C2H6 ${{\rm { \propto }}}$ θ X1 2 , respectively, where θ X1 is the coverage of X 1 characterized by the Langmuir adsorption isotherm‐like P CH4 ‐dependence as follows: θX1=PCH4normalPCH44pt+4ptK-1 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\theta }_{{X}_{1}}{\rm { =}}{{{{\rm { P}}}_{{{\rm { CH}}}_{{\rm { 4}}}}}\over{{{\rm { P}}}_{{{\rm { CH}}}_{{\rm { 4}}}}{\rm { \ +\ }}{{\rm { K}}}^{{\rm \ }-{\rm { 1}}}}}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, widespread interest has been aroused in converting methane into high value-added chemicals through photocatalytic oxidative or non-oxidative way, which can not only promote the development of clean energy but also effectively achieve the purpose of environmental protection by consuming greenhouse gases 1 10 . Researchers have used various strategies to improve the efficiency of photocatalytic methane conversion, such as introducing other auxiliary oxidants 11 15 , heat-assisted photoreaction 16 , and improving the separation efficiency of photogenerated carriers 17 . Unfortunately, the photocatalytic methane conversion efficiency is still commonly low, especially for the non-oxidative methane coupling (NOCM) reaction due to the much easier photocatalyst deactivation in the absence of oxidants 18 , 19 , which however is more desirable considering the high carbon-atom efficiency and less CO 2 emission.…”
Section: Introductionmentioning
confidence: 99%
“…67 68 Sugimoto and co-workers recently reported that methyl radicals would be stabilized on an SP surface, which would also be affected by H 2 O molecules adsorbed on the surface, based on their theoretical calculations. 69 Thus, the water content of the reaction mixture should be carefully optimized 37 for efficient and selective β-scission.…”
Section: Discussionmentioning
confidence: 99%